Ayurvedic Approaches to Holistic Management of Polycystic Ovary Syndrome (PCOS) - Ashvini D. Pardhekar; Rohit Waskar; Abhilash Pardhekar; Mayuri Deshpande (Journal of Pharmacy and Bioallied Sciences)
The female reproductive system relies on the intact uterine adnexa and the hypothalamic-pituitary-ovarian axis. An imbalance can lead to pathogenesis. PCOS is characterized by ovarian cysts, hyperandrogenism, and irregular ovulation. Over time, it can lead to symptoms such as changes in menstruation, obesity, infertility, depression, and increased risk of diabetes, cardiovascular disease, and endometrial cancer. In Ayurveda, PCOS is a condition affecting Rasa, Rakta, and Medas, the three Dhatus. Rakta, Rasa, and Artavavaha are the Srotas that are implicated in this illness. Symptoms that may appear include Anartava (amenorrhea), Vandhyatwa, Pushpagni, and Abeeja Rutuchakra (an ovular hemorrhage). A 23-year-old woman presented at the outpatient department with complaints of irregular menstruation and rapid weight gain. An ultrasound revealed left-sided polycystic ovary syndrome (PCOS). Palliative treatments such as Kaklarakshak Yog, Trikatu, and Triphala Churna were administered for 2 months. The patient experienced a significant reduction in symptoms and a return to a normal menstrual cycle within two months.